THE EFFECT OF BUDGET PARTICIPATION, ASIMETRY INFORMATION AND BUDGET EMPHASIS ON BUDGETARY SLACK WITH LOCUS OF CONTROL AS MODERATING VARIABLES AT ISLAMIC UNIVERSITY OF SUMATERA UTARA (UISU) - Barus, Muhammad Joni (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objectives of the research were (1) to discover the influence of budgetary participation, asymmetric information, and budget emphasis on budgetary slack in UISU (Universitas Islam Sumatera Utara) and (2) to discover the influence of Locus of Control in moderating the correlation among budgetary participation, asymmetric information, and budget emphasis with budgetary slack in UISU. This is a causality research. The population was 122 questionnaires, only 100 of them were returned thus became the samples. The samples were taken by applying census technique in which the whole population was taken as the samples. The data consisted of primary data and were collected through survey method by distributing questionnaires to the head and employees of UISI. The research tested the data by using measurement model or outer model, structural model or inner model, and effect size for the moderating variable. The results of the research proved that (1) budgetary participation had a significantly negative influence, and asymmetric and budget emphasis did not have any influence on budgetary slack in UISU, and (2) locus of control was not able to moderate the correlation among budgetary participation, asymmetric information, and budget emphasis with budgetary slack in UISU.